Traumas leading to Dilemmas: A Feminine Psychological Analysis of Alex Michaelides’ The Silent Patient - Fatima, Bismia; Bashir, Saima (Pakistan Languages and Humanities Review, 2025)
The study is a complex examination of marital conflicts in Alex Michaelides’ The Silent Patient (2019), based on Karen Horney’s theory of Feminine Psychology as the framework guide. The psychological traumas of Alicia Berenson, the novel’s female protagonist, are central in decoding the intricacies of her broken marriage. A qualitative method and descriptive approach has been adopted to analyze the traumatic occurrences that cause the breakdown of the marriage and the resulting consequences. Through close reading of the narrative with reference to Horney’s theory that counters classical Freudian views on women's psychology, the study enlightens on the deep impacts of gender stereotypes and objectification in society. The study investigates how Alicia Berenson adapts to the outcome of her failed marriage, gaining insight into her personal journey of rebuilding and resilience. Female psyche, marriage dynamics, and societal influences on women’s roles in relationships can be better understood through such researches